1997
DOI: 10.3758/bf03205511
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of return in location- and identity-based choice decision tasks

Abstract: Three experiments were conducted to determine whether inhibition of return can be best characterized as an attentional or a motor phenomenon. In the first experiment, subjects made choice keypress responses to the location of a target (left or right) or the identity of the target (X or +) by pressing a left or right response key.In the second experiment, the display was rotated 90°so that there was no direct spatial mapping between the vertically aligned stimulus display and the horizontally aligned response k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
104
3
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 14 publications
7
104
3
1
Order By: Relevance
“…Thus, Klein and Taylor suggested that inhibition will occur only for detection responses and discrimination responses based on the spatial location of the target. There is, however, growing evidence that inhibition may be found for responses based solely on the identity of a target, indicating that inhibited spatially localized motor responses cannot provide a complete account for the inhibition found at cued locations (e.g., Chasteen & Pratt, 1999;Lupianez et al, 1997;Pratt et al, 1997).…”
Section: Inhibition Of Return At Multiple Locationsmentioning
confidence: 99%
“…Thus, Klein and Taylor suggested that inhibition will occur only for detection responses and discrimination responses based on the spatial location of the target. There is, however, growing evidence that inhibition may be found for responses based solely on the identity of a target, indicating that inhibited spatially localized motor responses cannot provide a complete account for the inhibition found at cued locations (e.g., Chasteen & Pratt, 1999;Lupianez et al, 1997;Pratt et al, 1997).…”
Section: Inhibition Of Return At Multiple Locationsmentioning
confidence: 99%
“…Although the oculomotor system appears to play an important role in IOR (e.g., Rafal et al, 1989;, 2000, there is also a great deal of evidence that attention is inhibited from returning to previously cued locations (e.g., Handy, Jha, & Mangun, 1999;Lupiáñez et al, 1997;McDonald, Ward, & Kiehl, 1999;Pratt et al, 1997). If it is assumed that attention and motor programming are achieved within a network, it may also be assumed that inhibition applied to a preoculomotor attentional map is passed on throughout the network, subsequently affecting other motor responses in addition to saccades.…”
Section: Ior: Inhibition In a Preoculomotor Attentional Mapmentioning
confidence: 99%
“…The cause is associated with the processes occurring on presentation of the cue, whereas its effects are measured by responses to a target, presented at the cued location or at an uncued location. A great deal of research has shown that after IOR has been generated, it affects both manual keypress responses (e.g., Lupiáñez, Milán, Tornay, Madrid, & Tudela, 1997;Posner & Cohen, 1984;Pratt, Kingstone, & Khoe, 1997;Rafal, Calabresi, Brennan, & Sciolto, 1989) and oculomotor responses (e.g., Abrams & Dobkin, 1994;Godijn & Theeuwes, 2002a;Klein & MacInnes, 1999;Rafal, Egly, & Rhodes, 1994).…”
mentioning
confidence: 99%
“…It is important to note that IOR at a location in space only follows after attention has shifted reflexively to that location (see Klein, 2000, for a review). Indeed, IOR does not follow a shift of attention that is directed endogenously (voluntarily; Posner & Cohen, 1984;Pratt, Kingstone, & Khoe, 1997), except in conditions in which participants endogenously prepare an eye movement (Rafal, Calabresi, Brennan, & Sciolto, 1989).…”
Section: Introductionmentioning
confidence: 99%